Asbab an-Nuzul dalam Kitab Tafsir al-Misbah Karya M. Quraish Shihab (Studi Terhadap Surah al-Baqarah) - Risqo Faridatul Ulya (Istinarah: Riset Keagamaan, Sosial dan Budaya, 2020)
Abstrak: Tulisan ini mebahas mengenai asbab an-Nuzul dalam tafsir al-Misbah dalam surat al-Baqarah. Asbab an-Nuzul merupakan peristiwa yang melatarbelakangi turunnya ayat-ayat Alquran. Baik itu berupa pertanyaan, pernyataan atau jawaban dari suatu hukum kejadian yang timbul dari kejadian tersebut. Metode yang diterapkan dalam tulisan ini adalah metode analisis-deskriptif. Tujuan dari tulisan ini akan mengungkap pengertian an-Nuzul asbab, biografi, sekilas tafsir kitab al-Misbah, berapa as-an-Nuzul asbab dalam tafsir al-Misbah, dan penggunaan -Nuzul asbab dalam tafsir al-Misbah. Hasil dari penelitian ini adalah asbab an-Nuzul dalam kitab tafsir al-Misbah terdapat 7 ayat di dalam surat al-Baqarah yang berjumlah 286 ayat. Dalam kitab tafsir al-Misbah M. Quraish Shihab tidak memberikan secara detail mengenai asbab an-Nuzul di kitab tafsirnya. Karena masing-masing ayat dalam Alquran yang turun dan sampai Nabi Muhammad Saw. tidak sepenuhnya ada kausalitas dalam ayat tersebut. Dan M. Quraish Shihab juga menekankan penafsirannya dengan pendekatan bahasa, dan dalam setiap tulisan dan tafsir penulis pasti memiliki batasan atau fokus kajian dalam menafsirkan Alquran agar dapat mencapai sasaran yang diinginkan oleh penulis dengan cara melihat situasi dan kondisi. ketika dia menafsirkan Alquran, kitab tafsir Misbah.Kata Kunci: Asbab an-Nuzul, kitab tafsir al-Misbah dan surah al-Baqarah.                                                                         Abstract: This paper discusses the asbab an-Nuzul in the interpretation of al-Misbah in surah al-Baqarah. Asbab an-Nuzul is an event or event that lies behind the descending verses of the Alquran. Whether it is in the form of questions, statements or answers from a law of events arising from the incident. The method used in this paper is descriptive-analysis method. The purpose of this paper will reveal the definition of an-Nuzul asbab, biography, a glimpse of the book of interpretation of al-Misbah, how many as-an-Nuzul asbab in the interpretation of al-Misbah, and the use of an-Nuzul asbab in the interpretation of al-Misbah. The result of this research is asbab an-Nuzul in the book of tafsir al-Misbah, there are 7 verses in Surah al-Baqarah, totaling 286 verses. In the commentary book al-Misbah M. Quraish Shihab does not provide details about the asbab an-Nuzul in his commentary book. Because each verse in the Koran that came down and reached the Prophet Muhammad. there is absolutely no causality in the verse. And M. Quraish Shihab also emphasizes his interpretation with a language approach, and in every writing and interpretation the writer must have a limitation or focus of study in interpreting the Koran in order to achieve the goals desired by the author by looking at the situation and conditions. when he interprets the Koran, the Misbah commentary book.Keywords: Asbab an-Nuzul, kitab tafsir al-Misbah dan surah al-Baqarah